Prognostic significance of the pre-chemotherapy lymphocyte-to-monocyte ratio in patients with previously untreated metastatic colorectal cancer receiving FOLFOX chemotherapy - Lin, Gui-Nan (Chin J Cancer, 2016)
BACKGROUND: As a surrogate marker of systemic inflammation, the lymphocyte-to-monocyte ratio (LMR) is an independent prognostic factor for various malignancies. This study investigated the prognostic significance of the pre-chemotherapy LMR in patients with previously untreated metastatic colorectal cancer (mCRC) receiving chemotherapy. METHODS: The present study included newly diagnosed mCRC patients treated between January 2005 and December 2013 with FOLFOX chemotherapy, specifically oxaliplatin 180 mg/m(2) on day 1, with leucovorin 400 mg/m(2) administered as a 2-hour infusion before the administration of 5-fluorouracil 400 mg/m(2) as an intravenous bolus injection, and 5-fluorouracil 2400 mg/m(2) as a 46-h infusion immediately after 5-fluorouracil bolus injection. The LMR was calculated as the absolute count of lymphocytes divided by the absolute count of monocytes. COX proportional hazards analysis was performed to evaluate the association of LMR with survival outcomes. RESULTS: A total of 488 patients were included. Patients with high pre-chemotherapy LMR experienced significant improvements in progression-free survival (PFS, 9.2 vs. 7.6 months, P < 0.001) and overall survival (OS, 19.4 vs. 16.6 months, P < 0.001) compared with patients with low pre-chemotherapy LMR. Subsequent COX multivariate analysis showed that high pre-chemotherapy LMR (≥3.11) was an independent favorable prognostic factor for PFS and OS. Additionally, patients whose LMR remained high (high–high subgroup), increased (low–high subgroup), or decreased (high–low subgroup) following chemotherapy showed better results in terms of PFS and OS than patients whose LMR remained low (low–low subgroup) after chemotherapy. CONCLUSIONS: For patients with previously untreated mCRC receiving FOLFOX chemotherapy, an elevated pre-chemotherapy LMR is an independent favorable prognostic factor for PFS and OS, and changes in the LMR before and after chemotherapy seem to predict the benefit of chemotherapy.